STANDAR PROSES PEMBELAJARAN SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN MADRASAH IBTIDAIYAH - Oktavia Dwi Rahma Putri, Firzani; Alfi Husniyah, Fitri; Maulidya Putri Ponijan, Rizky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the standards of the learning process as an effort to improve the quality of education in MIN 2 Malang City. This research uses a qualitative case study approach, where the researcher understands the standards of the learning process at MIN 2 Malang City in depth. Data collection techniques used were interviews, observation and documentation. The data analysis used is the Huberman model including data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the learning process standards at MIN 2 Malang City are in accordance with the National Education Standards (SNP). Process standards include planning, implementation and assessment. When all these aspects are fulfilled it will improve the quality of education provided to students. These standards help students receive a quality education and ensure that the education provided meets established standards. By following good and appropriate educational process standards, educational institutions can create an environment that supports improving the quality of education.